Peran Negara Hukum dan Lembaga Penegakan Hukum Terhadap Kasus Pelecehan Seksual Bagi Perempuan dan Anak - Liana, April; Cordias, David Miseri; Z, Zulkarnain (Media Hukum Indonesia (MHI), 2024)
The state law and it’s application in cases of sexual abuse against women and children are covered in this publication. The aim of this research is to determine the methods used to prevent and combat sexual violence as well as the way in which the supremacy legal system is implemented in these situations. A review of the relevant literature and data analysis from a variety of sources are the methods of analysis employed. The findings demonstrate that the rule of law, through legislation, rules, and efficient execution of the law, has a significant benefit in application of the law to situations of sexual violence. Public awareness and education are also crucial components in the fight against sexual harassment. The research’s implications include the necessity of cooperation between the community, law enforcement, and the legal system in order to avoid and uphold the law against sexual harassment cases and ensure that everyone lives in a safe and equitable environment.